Teaching English in Sub-Departments: Challenges and Solutions - Azim, Yalda (Journal of Social Sciences - Kabul University, 2020)
This study examines the challenges faced by teachers in teaching English in sub-departments. A group of English department instructors with diverse teaching experiences in sub-departments was interviewed to gain insights into the difficulties they encounter. The analysis of the collected data revealed several key challenges, including large class sizes, multi-level classrooms, outdated and insufficient teaching materials, and limited instructional time for English courses. Based on the teachers' feedback, this study proposes several solutions to improve English instruction in sub-departments. These recommendations include establishing a dedicated committee to develop a specialized curriculum, designing English for Specific Purposes (ESP) courses, providing teacher training on modern instructional approaches, and implementing peer-teaching programs where students assist in faculties with high teaching demands.